PERBEDAAN PEMAHAMAN BELAJAR ANAK USIA PRASEKOLAH DAN USIA SEKOLAH - Della Raymena Jovanka (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2014)
This research measured the understanding of learning based on the theory of mind in the groups of pre-school aged and school aged children in two studies. Study 1 measured the spontaneous expression of 8 children from the two groups using the categories of resource, process, and learning content and intention, desire, and attention through secondary data in the language analysis CHILDES. The research conducted in March 2011 through May 2012 discovered at “tempat kursus membaca & menulis GAFA Tebet and SDN Gunung 05 (Mexico) South of Jakarta, the spontaneous expression about intention decreased. The expression of attention did not change. The second study measured the responds of 130 children to the story containing intention, desire, and attention. The result was a significant difference in the understanding of learning process based on the theory of mind in both groups. The pre-school aged children understood learning process and intention, while the school aged children understood learning process based on desire.